2010
DOI: 10.1002/acr.20033
|View full text |Cite
|
Sign up to set email alerts
|

Gait changes in patients with knee osteoarthritis are replicated by experimental knee pain

Abstract: Objective. Medial knee osteoarthritis (OA) is characterized by pain and associated with abnormal knee moments during walking. The relationship between knee OA pain and gait changes remains to be clarified, and a better understanding of this link could advance the treatment and prevention of disease progression. This study investigated changes in knee moments during walking following experimental knee pain in healthy volunteers, and whether these changes replicated the joint moments observed in medial knee OA p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
116
2
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 151 publications
(126 citation statements)
references
References 49 publications
7
116
2
1
Order By: Relevance
“…All subjective measurements were correlated (|r| C 0.54) with one another (Table 3), as were most of the objective measurements (|r| C 0.56) except for the peak knee adduction moment which did not correlate with any variable. The lack of correlation of the peak adduction moment to VAS knee pain and other variables was puzzling as it was contrary to the expected outcomes based on several previous reports [29,30,36,37]. However, other researchers also have observed a lack of correlation of knee adduction moment with knee pain, and other variables pertinent in knee OA.…”
Section: Discussionmentioning
confidence: 60%
“…All subjective measurements were correlated (|r| C 0.54) with one another (Table 3), as were most of the objective measurements (|r| C 0.56) except for the peak knee adduction moment which did not correlate with any variable. The lack of correlation of the peak adduction moment to VAS knee pain and other variables was puzzling as it was contrary to the expected outcomes based on several previous reports [29,30,36,37]. However, other researchers also have observed a lack of correlation of knee adduction moment with knee pain, and other variables pertinent in knee OA.…”
Section: Discussionmentioning
confidence: 60%
“…It has recently been demonstrated that patients with knee OA who have quadriceps activation failure acquire greater volitional quadriceps activation and muscle strength gain from an intervention aimed at blocking pain sensation centrally in combination with exercise (49). Second, the average pain intensity was 16.2 mm, which is lower than that reported in previous studies (25)(26)(27)36). The time course of experimental IPFP pain shows that maximum pain intensity is reached within 5 minutes, and then gradually declines over the following 10 -12 minutes (23).…”
Section: Discussionmentioning
confidence: 78%
“…Clinical knee joint pain arises from several structures, including the IPFP, and is a significant source of pain in patients with knee OA (47,48). Furthermore, experimental pain from the IPFP has been shown to change motor functions similar to those identified in knee pathology (22,23,25,26). However, experimental pain does not replicate the long-term aspects of clinical pain, including the psychosocial features.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pain associated with knee OA has been thought to result in gait modification as an attempt to reduce the load on the affected joint, with studies reporting changes in joint loading as a response to pain relief (22)(23)(24), or pain induction in experimental trials (25,26). Given that an increase in inflammatory markers can promote pain, it may also affect muscle function during gait, leading to different gait strategies to reduce joint load.…”
Section: Introductionmentioning
confidence: 99%